The attitude of university students about advertising on Facebook in the category of clothing and accessories - Bravo, Karina García (2022)
In recent years, the increase in social networks has led consumers to spend a lot of time online, getting a lot of information about different products and services that are of interest to them. It is in this context that companies have reoriented their strategies, in order to use social networks as a new means of advertising communication. There are different social networks such as Facebook, Twitter and Instagram; however, Facebook is one of the social networks that has taken great strength in recent years and companies have had to direct their advertising communications towards this medium. There is research that focuses on consumer attitudes towards advertising on Facebook. However, we found little literature that addresses this same issue focusing on the young consumer and a specific product category. In this context, this exploratory study focuses on understanding young women’s attitudes towards advertising in the clothing and accessories category presented on Facebook. To this end, fourteen interviews were conducted with university students in the city of Lima, selected on the basis of convenience sampling, which revealed that despite the fact that young university women have other social networks, they still use Facebook and show a positive attitude towards advertising on Facebook as long as the advertising is not invasive, entertains them, has relevant information, uses images that generate affinity with them and contains attractive messages according to their age.